Lessons on methodologies to assess women’s empowerment from two agricultural and livestock project portfolios - Malapit, Hazel J.; Galiè, Alessandra; Ferguson, Nathaniel; Njiru, Nelly; Omondi, Immaculate A.; Muchiri, Caroline; Lecoutere, Els (CGIAR Accelerator on Gender Equality and Inclusion, 2025)
To assess broader trends and impacts on women’s empowerment through agricultural development interventions, there is a need to compare projects and their impacts. This paper is based on the experiences of the Cultivate Africa’s Future (CultiAF) and the Livestock Vaccine Innovation Fund (LVIF) project portfolios implemented in African and Asian countries. We draw lessons from the constraints and opportunities of using standardized tools for measuring women’s empowerment, such as the project-level Women’s Empowerment in Agriculture Index (pro-WEAI) and the Women’s Empowerment in Livestock Index (WELI) tools. We also make recommendations for the improvement of these tools and their use. We conclude that, while these tools measure individual and household-level empowerment, complementary methods are needed to capture broader societal changes. The length of the tools has resulted in concerns about respondent fatigue, but balancing the need for comprehensive data with respondent burden is important. Streamlined versions of the pro-WEAI and the WELI could be useful for projects not primarily focused on empowerment. Proper interpretation of empowerment data is emphasized in this paper, with comparisons across time, gender and projects identified as being key to meaningful insights. The paper also underscores the importance of consistent measurement to ensure valid results. These learnings can inform improvement of the tools to better identify the best approaches to support women’s empowerment in agriculture and livestock. The learnings will also be useful for development and research organizations implementing portfolios of projects with women’s empowerment objectives and for developers of pro-WEAI tools, WELI tools and similar tools for measuring women’s empowerment.